Recommendations for Tobacco Control on Post-Secondary Campuses that are Geographically Isolated - Alain P. Gauthier; Sandra C. Dorman; Elizabeth F. Wenghofer; Véronique M. Charbonneau; Caroline Y. Dignard; Danika L. Fleury (Tabriz University of Medical Sciences, 2013)
Background: Many Ontarians continue to report exposure to second-hand smoke in public spaces. Completely smoke-free environments are the preferred and socially responsible option for non-smoking policies; however, when considering the variety of landscapes in which post-secondary institutions are located, "a one size fits all‟ smoking policy is unrealistic to implement and en-force. The purpose of the study was to: 1) gain a better sense of the prevalence of smoking and exposure to second-hand smoke in a post-secondary context that is geographically isolated; 2) assess the awareness of existing non-smoking initiatives; and 3) identify preferred approaches for tobacco control. Methods: An online survey was distributed in 2012 to all members of the Laurentian University community. Descriptive statistics are presented, using frequency distributions, and group comparisons are reported, using Chi-Square analyses. Results: A total of 1282 persons completed the survey. Nearly 80% of respondents reported that they had been exposed to second-hand smoke in the past month on campus and the majority of respondents felt that smoking should only be allowed in Designated Outdoor Smoking Areas (51.5%); including 37.3% of daily smokers and occasional smokers. Conclusion: Institutions with a geographically isolated campus, which limit options to divert smokers from public entrances, should consider the use of Designated Outdoor Smoking Areas. Implementation will create immediate reductions in the prevalence of smoking at building entrances and in high traffic locations and will therefore protect non-smokers from the dangers of environmental tobacco smoke.